Improving the use of LLMs in radiology through prompt engineering: from precision prompts to zero-shot learning - Russe, Maximilian Frederik; Reisert, Marco; Bamberg, Fabian; Rau, Alexander (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
Purpose Large language models (LLMs) such as ChatGPT have shown significant potential in radiology. Their effectiveness often depends on prompt engineering, which optimizes the interaction with the chatbot for accurate results. Here, we highlight the critical role of prompt engineering in tailoring the LLMs’ responses to specific medical tasks.Materials and Methods Using a clinical case, we elucidate different prompting strategies to adapt the LLM ChatGPT using GPT4 to new tasks without additional training of the base model. These approaches range from precision prompts to advanced in-context methods such as few-shot and zero-shot learning. Additionally, the significance of embeddings, which serve as a data representation technique, is discussed.Results Prompt engineering substantially improved and focused the chatbot’s output. Moreover, embedding of specialized knowledge allows for more transparent insight into the model’s decision-making and thus enhances trust.Conclusion Despite certain challenges, prompt engineering plays a pivotal role in harnessing the potential of LLMs for specialized tasks in the medical domain, particularly radiology. As LLMs continue to evolve, techniques like few-shot learning, zero-shot learning, and embedding-based retrieval mechanisms will become indispensable in delivering tailored outputs.Key Points Citation Format
Keywords: radiology; artificial Intelligence; natural Language Processing